Analysis of adhesion molecules in the immunopathogenesis of giant cell arteritis. Issue 6 (June 1991) - Wawryk, S O; Ayberk, H; Boyd, A W; Rode, J
Abstract : To explore the role of adhesion molecules in mediating mononuclear cell localisation, development of the granulomatous reaction, and cell mediated damage to the arterial wall in giant cell arteritis, 17 temporal artery biopsy specimens were examined. Eleven showed the histological features of giant cell arteritis and six showed no evidence of arteritis. All were examined for the expression of LFA-3, ICAM-1 and its receptor LFA-1, and HLA-DR. Temporal arteries with early features of arteritis, as well as histologically unaffected skip areas, showed a regional induction of ICAM-1 expression, but not HLA-DR, on smooth muscle cells of the media. ICAM-1 expression was detected in areas where a clinically important mononuclear cell infiltrate had not yet developed. In more florid cases of giant cell arteritis there was an additional widespread induction of ICAM-1 expression on intimal myofibroblasts. Strong expression of ICAM-1, HLA-DR, and LFA-3 was found on macrophages, epithelioid cells, and giant cells comprising the granulomatous lesion. The pattern of expression of these adhesion molecules suggests that they have a role in leucocyte traffic into the vascular lesion as well as in mediating the intercellular interactions which constitute the granulomatous response.